Apoptosis during arenavirus infection: mechanisms and evasion strategies - Meyer, Bjoern; Groseth, Allison (Microbes and infection, 2018)
In recent years there has been a greatly increased interest in the interactions of arenaviruses with the apoptotic machinery, and particularly the extent to which these interactions may be an important contributor to pathogenesis. Here we summarize the current state of our knowledge on this subject and address the potential for interplay with other immunological mechanisms known to be regulated by these viruses. We also compare and contrast what is known for arenavirus-induced apoptosis with observations from other segmented hemorrhagic fever viruses.